Teenage Marriage in Post Conflict Northern Uganda: A Case of Amuru District - Ouma, Simple; Odong Obita, Kenneth; Turyasima, Mananura; Harriet Omara, Acca; Nabbale, Florence; Rama, Moses Toe; Adong, Caroline Cephas; Odongkara, Mpora Beatrice; Igwaro Odongo-Aginya, Emmanuel; Awor, Silvia (Science Journal of Public Health, 2018)
Background: Teenage marriage eventually lead to teenage pregnancy with all it associated adverse consequences. Moreover, teenagers are less likely to utilize antenatal care and as well exhibit sub-optimal neonatal care compared to adult women. Thus, the need to report on teenage marriage in order to inform policy makers to provide necessary teenage sexual reproductive health services with relevant policies especially in post-conflict settings like Northern Uganda. Objectives: To describe prevalence and determinants of teenage marriage in post-conflict Northern Uganda. Methods: In this cross-sectional study, data was collected from 424 females of reproductive age using pre-tested semi-structured questionnaires. Univariate and bivariate analyses were carried out using SPSS 16.0. Results: Mean age of study participants was 27 years. Majority of participants (79.0%) and their husbands (67.2%) were peasant farmers. Majority of participants were married (85.8%) with about one-fifth (18.1%) of the participants pregnant at the time of interview. Among the married participants, majority of the participants (65.1%) and their husbands (64.2%) had only primary education. Majority (86.3%) of the married women first got married as teenagers. Mean age at first marriage was 17 years. Women in this population generally got married at early ages. Women who got married at younger ages were lowly educated and generally never had formal paid employments. Likewise, women who got married at younger ages were generally married to lowly educated men with no formal employments. In contrast, women who married later in life had better education and married men with better education level and above all such couples tend to engage in formal paid employments. In addition, women who got married at older ages had less number of live births and desired to give birth to less children than women who got married at younger ages. Conclusions: Women in post-conflict Northern Uganda are experiencing high level of teenage marriage. This put them at risk of not attaining necessary education and employable skills hence poverty. This calls for targeted interventions from both government and development partners in order to reverse the current trend in teenage marriage due to inequality in formal education and other social amenities and thus save the girl child from poverty.
Keywords: Teenage Marriage; Age at First Marriage; Rural Women; Post Conflict Settings